Cam Deformities and Limited Hip Range of Motion Are Associated With Early Osteoarthritic Changes in Adolescent Athletes: A Prospective Matched Cohort Study - Cody C. Wyles; Germán A. Norambuena; Benjamin M. Howe; Dirk R. Larson; Bruce A. Levy; Brandon J. Yuan; Robert T. Trousdale; Rafael J. Sierra (The American Journal of Sports Medicine, 2017)
Background: The natural history of femoroacetabular impingement (FAI) remains incompletely understood. In particular, there is limited documentation of joint damage in adolescent patients with limited range of motion (LROM) of the hip, which is commonly associated with FAI. Purpose: To evaluate changes in magnetic resonance imaging (MRI), radiographs, and clinical examinations over 5 years in a group of athletes from a wide variety of sports with asymptomatic LROM of the hip compared with matched controls. Study Design: Cohort study (prognosis); Level of evidence, 2. Methods: The authors screened 226 male and female athletes aged 12 to 18 years presenting for preparticipation sports physical examinations. Using a goniometer, we identified 13 participants with at least one hip having internal rotation 55° on lateral radiographs) was present in 20 of 22 hips (91%) in the LROM group and 12 of 26 hips (46%) in the control group ( P = .0165). The following variables at baseline were associated with an increased risk of degenerative changes at 5-year follow-up for the entire cohort: decreased hip internal rotation, positive anterior impingement sign, decreased hip flexion, increased alpha angle, and presence of a cam lesion. Conclusion: At 5 years, young athletes with LROM of the hip showed increased progressive degenerative changes on MRI and radiographs compared with matched controls. Although the majority of these participants remained asymptomatic, those with features of FAI had radiographic findings consistent with early osteoarthritis. These outcomes suggest that more aggressive screening and counseling of young active patients may be helpful to prevent hip osteoarthritis in those with FAI.